O salário maternidade à luz do princípio da universalidade da cobertura e do atendimento - Oliveira, Katia Cristine Santos de (2005)
The aim of this work is to analyze the benefit of the maternity salary according to the universality of the covering and serving principle and also the consequences of its application in the real world. The maternity protection is the target of the analysis. It comes from the necessity of the pregnant when she gives birth to her child and from her impossibility to work during the early days of her newborn baby life. This work was realized based on bibliographic researches, law books and nonlaw ones, and articles related to the topic of this study. Superior Courts decisions were analyzed. Historic facts of the maternity protection were also emphasized, since the Convention 03 of the Work International Organization to the present documents in attention to the importance of the quality to be mother. The maternity protection and the maternity salary are ensured not only by the Brazilian Constitution but also by the present welfare laws. When 1988 Brazilian Constitution describes the equality like the main principle for the legislator and the interpreter it becomes impossible that the common legislator makes laws without observing the constitutional side. As a consequence, the subconstitutional legislator is not able to establish different treatment to the same fact: the maternity